Preparation method of Zr-Nb alloy for dual-action hip joint

By introducing elements such as Mo, Ti, Si and Sn into the Zr-Nb alloy and adopting a specific process flow, a double-moving hip Zr-Nb alloy with excellent corrosion and wear resistance is prepared, which solves the problems of low surface hardness, poor wear resistance and high elastic modulus of the existing alloys, and achieves higher biomedical performance and service life.

CN119120988BActive Publication Date: 2025-03-14SOUTHERN MEDICAL UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411276181.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2025-03-14
Estimated Expiration
2044-09-12

AI Technical Summary

Technical Problem

The existing Zr-2.5Nb alloy has low surface hardness, poor wear resistance, and its elastic modulus is higher than that of human bones. Long-term implantation of human bodies may cause bone damage.

Method used

By introducing elements such as Mo, Ti, Si and Sn into the Zr-Nb alloy, and using vacuum smelting, solid solution, quenching and crystal annealing, a double-moving hip Zr-Nb alloy with excellent corrosion resistance and wear resistance is prepared.

Benefits of technology

It improves the surface hardness and wear resistance of the alloy, reduces the elastic modulus, meets the application requirements of the biomedical field, and improves the service life during human implantation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005040250840000161
    Figure BDA0005040250840000161
Patent Text Reader

Abstract

The invention discloses a preparation method of a dual-action hip joint Zr-Nb alloy, the Zr-Nb alloy includes Nb 1.0-2.5%, Mo 0.3-1%, Ti 0.7-1.2%, Si 0.2-0.6%, Sn 1.0-2.0%, and the balance is Zr; the preparation method includes preparing a master alloy designed as follows, and the master alloys are all melted and cast into ingots under a vacuum protective atmosphere. The above-mentioned preparation method adopts the method of first preparing the master alloy, then subjecting the master alloy to vacuum melting, secondary feeding and other steps, making each component uniform and the temperature uniform, and finally subjecting the master alloy to solid solution, quenching, intermediate annealing and crystallization annealing, so as to realize multiple strengthening mechanisms such as solid solution strengthening, fine grain strengthening, and second phase strengthening, and generate a passive oxide on its surface, and improve its corrosion resistance and wear resistance on the basis of ensuring the biocompatibility of the alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of Zr-Nb alloys, and in particular to a method for preparing a double-action hip joint Zr-Nb alloy. Background Art

[0002] The dual-motion hip joint is usually composed of an acetabulum component and a femoral component, and is generally made of titanium alloy, cobalt-chromium-molybdenum, stainless steel, ultra-high molecular weight polyethylene, ceramics and other materials. It is designed according to the morphology, structure and function of the human hip joint, replaces one or two articular surfaces of the hip joint, and limits its translation and rotation in one or more planes through the geometry of the articular surfaces.

[0003] Zr-Nb alloy is a binary alloy composed of zirconium and niobium. Its basic composition is Zr-1%Nb and Zr-2.5Nb%. This alloy has good corrosion resistance, especially in high temperature and high pressure water and steam environment of 300-400℃, its corrosion resistance and mechanical properties are excellent, and the corrosion resistance and mechanical properties of Zr-Nb alloy are due to its unique microstructure and passive oxide formed on the surface. Studies have shown that the solubility and corrosion resistance of this alloy are closely related to the microstructure of its precipitation and the solute content of the α matrix. Through different thermal annealing treatments, fine structures and surface passive oxides with excellent corrosion resistance can be produced. At present, Zr-Nb alloys are gradually used in biomedical implant materials, especially Zr-2.5Nb alloys, because of their good mechanical properties, corrosion resistance and good biocompatibility. However, the surface hardness of Zr-2.5Nb alloy is relatively low and its wear resistance is poor, which restricts its wide application in artificial joints. In addition, when Zr-2.5Nb alloy is used in the biomedical field, because its elastic modulus (greater than 70Gpa) is higher than that of human bones, it will cause mismatch when implanted in the human body for a long time. Especially when the exercise is too intense, it is easy to cause damage to personal bones. In severe cases, it may even cause bone fractures. Therefore, the elastic modulus of the material needs to be further reduced. Summary of the invention

[0004] In order to overcome the deficiencies of the prior art, the present invention provides a method for preparing a dual-motion hip joint Zr-Nb alloy to solve the above-mentioned traditional technical problems.

[0005] The present invention is implemented by the following technical solutions:

[0006] A preparation method of a dual-action hip joint Zr-Nb alloy, wherein the dual-action hip joint Zr-Nb alloy comprises the following components in weight percentage:

[0007] Nb 1.0-2.5%, Mo 0.3-1%, Ti 0.7-1.2%, Si 0.2-0.6%, Sn 1.0-2.0%; the balance is Zr and its inevitable impurities;

[0008] The preparation method comprises the following preparation steps:

[0009] S1: preparing the following master alloys respectively: 10%wt% zirconium-niobium alloy, 10%wt% zirconium-molybdenum alloy, 10%wt% zirconium-titanium alloy, 10%wt% zirconium-silicon alloy, and 10%wt% zirconium-tin alloy; the above master alloys are melted and cast into ingots under vacuum protective atmosphere;

[0010] S2: Weigh the following components by weight:

[0011] 28-68 parts of oxygen-free pure zirconium, 10-25 parts of zirconium-niobium alloy, 3-10 parts of zirconium-molybdenum alloy, 7-12 parts of zirconium-titanium alloy, 2-6 parts of zirconium-silicon alloy, 10-20 parts of zirconium-tin alloy;

[0012] Place oxygen-free pure zirconium, zirconium-niobium alloy, zirconium-molybdenum alloy and zirconium-titanium alloy prepared in proportion in the graphite crucible of the vacuum granulator melting chamber, and place zirconium-silicon alloy and zirconium-tin alloy in the secondary feeding hopper; place the raw materials and intermediate alloy in the graphite crucible, evacuate to 10Pa-20Pa, and then fill with industrial pure argon; heat up to 2650℃-2700℃, wait for the furnace charge to be completely melted, stir the molten metal by a mechanical stirring device to make its temperature and composition uniform; then cool down to 2 000℃~2200℃, start the secondary feeding device, add the zirconium-silicon alloy and the zirconium-tin alloy, and after the charge is melted, start the mechanical stirring device to make the metal liquid composition and temperature uniform; then, cool the temperature to 1000℃~1200℃, keep it warm for 1h-1.5h to obtain an alloy ingot; then, carry out solution treatment, quenching treatment and intermediate annealing treatment on the alloy ingot, and forge it into a billet of the desired shape (such as a double-action hip joint); finally, carry out crystallization annealing treatment to obtain it.

[0013] In the present invention, Zr (zirconium) is a basic component element of the alloy and also shows good biocompatibility in the biomedical field. Zirconium has excellent corrosion resistance to various acids, alkalis and salts, and can react with various elements at high temperatures to form solid solutions, which makes it possible to be used as an alloy element to improve the properties of other metals.

[0014] Nb (niobium), the addition of niobium helps to improve the plasticity and processing properties of zirconium alloys, and can also improve the oxidation resistance and alkali metal corrosion resistance of zirconium alloys.

[0015] Mo (molybdenum), the addition of molybdenum can refine the grains, enhance the hardness and strength of the alloy, and thus improve the wear resistance. At the same time, the combination of Mo and Nb can further increase the wear resistance of the alloy, but a high content will reduce the fracture toughness of the alloy.

[0016] Ti (titanium), the addition of titanium can react with Zr and Nb to form stronger bonds and play a role in solid solution strengthening, but when the content is high, it will reduce the heat resistance of the alloy.

[0017] Si (silicon), adding trace amounts of Si elements can refine the second phase particles, reduce the alloy recrystallization degree, and increase the strength and hardness of the alloy. However, when the content is high, it will reduce the plasticity of the alloy and make the alloy more prone to cracking during processing.

[0018] Sn (tin) can effectively improve the corrosion resistance of the alloy and reduce the melting point of the alloy. However, if the content is too high, it will affect the toughness and plasticity of the alloy.

[0019] In summary, in view of the above-mentioned properties of Zr, Nb, Mo, Ti, Si and Sn, the dual-motion hip joint Zr-Nb alloy of the present invention is based on the Zr-Nb alloy, by introducing elements such as Mo, Ti, Si and Sn, to achieve multiple strengthening mechanisms such as solid solution strengthening, fine grain strengthening, and second phase strengthening. On the basis of ensuring the biocompatibility of the alloy, its surface hardness and wear resistance are improved. At the same time, elements such as Zr, Nb, Mo, Ti, Si and Sn are non-toxic and have no side effects to the human body. When implanted in the human body, they can effectively improve the wear resistance and thus increase its service life.

[0020] Further, the dual-motion hip joint Zr-Nb alloy includes the following components in weight percentage:

[0021] Nb 1.0-2.5%, Mo 0.5-0.8%, Ti 0.9-1.1%, Si 0.4-0.6%, Sn 1.0-2.0%, and the balance is Zr and inevitable impurities thereof.

[0022] Furthermore, the total content of the inevitable impurities does not exceed 0.1%.

[0023] Furthermore, the mass ratio of the Si to the Sn is 0.2-0.3, that is, the Si / Sn ratio is controlled between 0.2-0.3 to improve the metallurgical casting properties of the material.

[0024] Furthermore, in step S1, the oxygen-free pure zirconium is oxygen-free pure zirconium with a zirconium content of 99.95 wt%.

[0025] Further, in step S1, the zirconium-niobium alloy containing 10%wt% is prepared by using oxygen-free pure zirconium containing 99.95wt% zirconium and oxygen-free pure niobium containing 99.95wt% niobium;

[0026] The zirconium-molybdenum alloy containing 10%wt% is prepared by using oxygen-free pure zirconium containing 99.95wt% zirconium and oxygen-free pure molybdenum containing 99.95wt% molybdenum;

[0027] The zirconium-titanium alloy containing 10%wt% is prepared by oxygen-free pure zirconium containing 99.95wt% zirconium and oxygen-free pure titanium containing 99.95wt% titanium;

[0028] The zirconium-silicon alloy containing 10%wt% is prepared by oxygen-free pure zirconium containing 99.95wt% zirconium and oxygen-free pure silicon containing 99.95wt% silicon;

[0029] The zirconium-tin alloy containing 10%wt% is prepared by oxygen-free pure zirconium containing 99.95wt% zirconium and oxygen-free pure tin containing 99.95wt% tin.

[0030] Further, in step S2, the temperature of the solution treatment is 800°C-900°C, the time is 1h-3h, and the solution is water-cooled.

[0031] Furthermore, in step S2, the temperature of the quenching treatment is 800°C-900°C.

[0032] Furthermore, in step S2, the temperature of the annealing treatment is 600°C-700°C.

[0033] Further, in step S2, the temperature of the crystallization annealing treatment is 650°C-750°C.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] 1. The preparation method of the dual-action hip joint Zr-Nb alloy of the present invention is to first prepare an intermediate alloy, then subject the intermediate alloy to vacuum melting, secondary feeding and other steps to uniformize the components and temperature, and finally subject it to solid solution, quenching, intermediate annealing and crystallization annealing to achieve multiple strengthening mechanisms such as solid solution strengthening, fine grain strengthening, and second phase strengthening, and generate passive oxide on its surface, thereby improving its corrosion resistance and wear resistance while ensuring the biocompatibility of the alloy.

[0036] 2. The dual-motion hip joint Zr-Nb alloy of the present invention is based on the Zr-Nb alloy, and introduces elements such as Mo, Ti, Si and Sn to achieve multiple strengthening mechanisms such as solid solution strengthening, fine grain strengthening, and second phase strengthening. On the basis of ensuring the biocompatibility of the alloy, its surface hardness is improved. At the same time, elements such as Zr, Nb, Mo, Ti, Si and Sn are non-toxic and have no side effects to the human body. When implanted in the human body, they can effectively improve the wear resistance and thus increase its service life.

[0037] 3. The tensile strength Rm of the dual-action hip joint Zr-Nb alloy of the present invention is greater than 650 MPa, and the elastic modulus is below 70 GPa, which meets the application requirements of dual-action hip joints and other biomedical fields. DETAILED DESCRIPTION

[0038] The present invention is further described below in conjunction with specific implementation methods. It should be noted that, under the premise of no conflict, the various embodiments or technical features described below can be arbitrarily combined to form a new embodiment.

[0039] Example 1

[0040] A preparation method of a dual-action hip joint Zr-Nb alloy, wherein the dual-action hip joint Zr-Nb alloy comprises the following components in weight percentage:

[0041] Nb 1.0%, Mo 0.5%, Ti 0.7%, Si 0.2%, Sn 1.0%; the balance is Zr and its inevitable impurities;

[0042] The preparation method comprises the following preparation steps:

[0043] S1: preparing the following master alloys respectively: 10%wt% zirconium-niobium alloy, 10%wt% zirconium-molybdenum alloy, 10%wt% zirconium-titanium alloy, 10%wt% zirconium-silicon alloy, and 10%wt% zirconium-tin alloy; the above master alloys are melted and cast into ingots under vacuum protective atmosphere;

[0044] Specifically, each master alloy is melted in a vacuum induction granulator, firstly vacuumed to 10Pa, then filled with argon gas to 1.0atm, and when all the metal materials are melted, mechanical stirring is used to make the metal liquid uniform in composition and temperature, and the metal liquid is poured into a cold water pool for cooling to form metal beads;

[0045] S2: Weigh the following components by weight:

[0046] 66 parts of oxygen-free pure zirconium, 10 parts of zirconium-niobium alloy, 5 parts of zirconium-molybdenum alloy, 7 parts of zirconium-titanium alloy, 2 parts of zirconium-silicon alloy, and 10 parts of zirconium-tin alloy;

[0047] Place oxygen-free pure zirconium, zirconium-niobium alloy, zirconium-molybdenum alloy and zirconium-titanium alloy prepared in proportion in a graphite crucible of a vacuum granulator melting chamber, and place zirconium-silicon alloy and zirconium-tin alloy in a secondary charging hopper; place raw materials and intermediate alloys in a graphite crucible, evacuate to 10Pa, and then fill with industrial pure argon; heat up to 2700°C, wait for all the furnace charge to be completely melted, stir the molten metal by a mechanical stirring device to make its temperature and composition uniform; then cool down to 2000°C, start the secondary charging device, add zirconium-silicon alloy and zirconium-tin alloy, and start the mechanical stirring device after the furnace charge is melted to make the molten metal composition and temperature uniform; then cool down to 1000°C, keep warm for 1 hour, and obtain an alloy ingot; then, perform solid solution treatment, quenching treatment and intermediate annealing treatment on the alloy ingot to forge it into a billet of a desired shape; finally, perform crystallization annealing treatment to obtain the product.

[0048] Among them, the temperature of solution treatment is 850℃, time is 2h, and water cooling is used; the temperature of quenching treatment is 800℃; the temperature of annealing treatment is 700℃; and the temperature of crystallization annealing treatment is 650℃.

[0049] In the above steps, the oxygen-free pure zirconium is an oxygen-free pure zirconium with a zirconium content of 99.95wt%; the zirconium-niobium alloy containing 10wt% is prepared by oxygen-free pure zirconium with a zirconium content of 99.95wt% and oxygen-free pure niobium with a niobium content of 99.95wt%; the zirconium-molybdenum alloy containing 10wt% is prepared by oxygen-free pure zirconium with a zirconium content of 99.95wt% and oxygen-free pure molybdenum with a molybdenum content of 99.95wt%; the zirconium-titanium alloy containing 10wt% Gold is made of oxygen-free pure zirconium with a zirconium content of 99.95wt% and oxygen-free pure titanium with a titanium content of 99.95wt%; the zirconium-silicon alloy containing 10wt% is made of oxygen-free pure zirconium with a zirconium content of 99.95wt% and oxygen-free pure silicon with a silicon content of 99.95wt%; the zirconium-tin alloy containing 10wt% is made of oxygen-free pure zirconium with a zirconium content of 99.95wt% and oxygen-free pure tin with a tin content of 99.95wt%.

[0050] Example 2

[0051] A preparation method of a dual-action hip joint Zr-Nb alloy, wherein the dual-action hip joint Zr-Nb alloy comprises the following components in weight percentage:

[0052] Nb 1.0%, Mo 1.0%, Ti 1.2%, Si 0.4%, Sn 2.0%; the balance is Zr and its inevitable impurities;

[0053] The preparation method comprises the following preparation steps:

[0054] S1: preparing the following master alloys respectively: 10%wt% zirconium-niobium alloy, 10%wt% zirconium-molybdenum alloy, 10%wt% zirconium-titanium alloy, 10%wt% zirconium-silicon alloy, and 10%wt% zirconium-tin alloy; the above master alloys are melted and cast into ingots under vacuum protective atmosphere;

[0055] Specifically, each master alloy is melted in a vacuum induction granulator, firstly vacuumed to 10Pa, then filled with argon gas to 1.0atm, and when all the metal materials are melted, mechanical stirring is used to make the metal liquid uniform in composition and temperature, and the metal liquid is poured into a cold water pool for cooling to form metal beads;

[0056] S2: Weigh the following components by weight:

[0057] 44 parts of oxygen-free pure zirconium, 10 parts of zirconium-niobium alloy, 10 parts of zirconium-molybdenum alloy, 12 parts of zirconium-titanium alloy, 4 parts of zirconium-silicon alloy, and 20 parts of zirconium-tin alloy;

[0058] Place oxygen-free pure zirconium, zirconium-niobium alloy, zirconium-molybdenum alloy and zirconium-titanium alloy prepared in proportion in a graphite crucible of a vacuum granulator melting chamber, and place zirconium-silicon alloy and zirconium-tin alloy in a secondary charging hopper; place raw materials and intermediate alloys in a graphite crucible, evacuate to 10Pa, and then fill with industrial pure argon; heat up to 2700°C, wait for all the furnace charge to be completely melted, stir the molten metal by a mechanical stirring device to make its temperature and composition uniform; then cool down to 2000°C, start the secondary charging device, add zirconium-silicon alloy and zirconium-tin alloy, and start the mechanical stirring device after the furnace charge is melted to make the molten metal composition and temperature uniform; then cool down to 1000°C, keep warm for 1 hour, and obtain an alloy ingot; then, perform solid solution treatment, quenching treatment and intermediate annealing treatment on the alloy ingot to forge it into a billet of a desired shape; finally, perform crystallization annealing treatment to obtain the product.

[0059] Among them, the temperature of solution treatment is 850℃, time is 2h, and water cooling is used; the temperature of quenching treatment is 800℃; the temperature of annealing treatment is 700℃; and the temperature of crystallization annealing treatment is 650℃.

[0060] In the above steps, the oxygen-free pure zirconium is an oxygen-free pure zirconium with a zirconium content of 99.95wt%; the zirconium-niobium alloy containing 10wt% is prepared by oxygen-free pure zirconium with a zirconium content of 99.95wt% and oxygen-free pure niobium with a niobium content of 99.95wt%; the zirconium-molybdenum alloy containing 10wt% is prepared by oxygen-free pure zirconium with a zirconium content of 99.95wt% and oxygen-free pure molybdenum with a molybdenum content of 99.95wt%; the zirconium-titanium alloy containing 10wt% Gold is made of oxygen-free pure zirconium with a zirconium content of 99.95wt% and oxygen-free pure titanium with a titanium content of 99.95wt%; the zirconium-silicon alloy containing 10wt% is made of oxygen-free pure zirconium with a zirconium content of 99.95wt% and oxygen-free pure silicon with a silicon content of 99.95wt%; the zirconium-tin alloy containing 10wt% is made of oxygen-free pure zirconium with a zirconium content of 99.95wt% and oxygen-free pure tin with a tin content of 99.95wt%.

[0061] Example 3

[0062] A preparation method of a dual-action hip joint Zr-Nb alloy, wherein the dual-action hip joint Zr-Nb alloy comprises the following components in weight percentage:

[0063] Nb 1.5%, Mo 0.5%, Ti 0.8%, Si 0.2%, Sn 1.0%; the balance is Zr and its inevitable impurities;

[0064] The preparation method comprises the following preparation steps:

[0065] S1: preparing the following master alloys respectively: 10%wt% zirconium-niobium alloy, 10%wt% zirconium-molybdenum alloy, 10%wt% zirconium-titanium alloy, 10%wt% zirconium-silicon alloy, and 10%wt% zirconium-tin alloy; the above master alloys are melted and cast into ingots under vacuum protective atmosphere;

[0066] Specifically, each master alloy is melted in a vacuum induction granulator, firstly vacuumed to 10Pa, then filled with argon gas to 1.0atm, and when all the metal materials are melted, mechanical stirring is used to make the metal liquid uniform in composition and temperature, and the metal liquid is poured into a cold water pool for cooling to form metal beads;

[0067] S2: Weigh the following components by weight:

[0068] 60 parts of oxygen-free pure zirconium, 15 parts of zirconium-niobium alloy, 5 parts of zirconium-molybdenum alloy, 8 parts of zirconium-titanium alloy, 2 parts of zirconium-silicon alloy, and 10 parts of zirconium-tin alloy;

[0069] Place oxygen-free pure zirconium, zirconium-niobium alloy, zirconium-molybdenum alloy and zirconium-titanium alloy prepared in proportion in a graphite crucible of a vacuum granulator melting chamber, and place zirconium-silicon alloy and zirconium-tin alloy in a secondary charging hopper; place raw materials and intermediate alloys in a graphite crucible, evacuate to 10Pa, and then fill with industrial pure argon; heat up to 2700°C, wait for all the furnace charge to be completely melted, stir the molten metal by a mechanical stirring device to make its temperature and composition uniform; then cool down to 2000°C, start the secondary charging device, add zirconium-silicon alloy and zirconium-tin alloy, and start the mechanical stirring device after the furnace charge is melted to make the molten metal composition and temperature uniform; then cool down to 1000°C, keep warm for 1 hour, and obtain an alloy ingot; then, perform solid solution treatment, quenching treatment and intermediate annealing treatment on the alloy ingot to forge it into a billet of a desired shape; finally, perform crystallization annealing treatment to obtain the product.

[0070] Among them, the temperature of solution treatment is 850℃, time is 2h, and water cooling is used; the temperature of quenching treatment is 800℃; the temperature of annealing treatment is 700℃; and the temperature of crystallization annealing treatment is 650℃.

[0071] In the above steps, the oxygen-free pure zirconium is an oxygen-free pure zirconium with a zirconium content of 99.95wt%; the zirconium-niobium alloy containing 10wt% is prepared by oxygen-free pure zirconium with a zirconium content of 99.95wt% and oxygen-free pure niobium with a niobium content of 99.95wt%; the zirconium-molybdenum alloy containing 10wt% is prepared by oxygen-free pure zirconium with a zirconium content of 99.95wt% and oxygen-free pure molybdenum with a molybdenum content of 99.95wt%; the zirconium-titanium alloy containing 10wt% Gold is made of oxygen-free pure zirconium with a zirconium content of 99.95wt% and oxygen-free pure titanium with a titanium content of 99.95wt%; the zirconium-silicon alloy containing 10wt% is made of oxygen-free pure zirconium with a zirconium content of 99.95wt% and oxygen-free pure silicon with a silicon content of 99.95wt%; the zirconium-tin alloy containing 10wt% is made of oxygen-free pure zirconium with a zirconium content of 99.95wt% and oxygen-free pure tin with a tin content of 99.95wt%.

[0072] Example 4

[0073] A preparation method of a dual-action hip joint Zr-Nb alloy, wherein the dual-action hip joint Zr-Nb alloy comprises the following components in weight percentage:

[0074] Nb 2.0%, Mo 0.3%, Ti 0.7%, Si 0.2%, Sn 1.0%; the balance is Zr and its inevitable impurities;

[0075] The preparation method comprises the following preparation steps:

[0076] S1: preparing the following master alloys respectively: 10%wt% zirconium-niobium alloy, 10%wt% zirconium-molybdenum alloy, 10%wt% zirconium-titanium alloy, 10%wt% zirconium-silicon alloy, and 10%wt% zirconium-tin alloy; the above master alloys are melted and cast into ingots under vacuum protective atmosphere;

[0077] Specifically, each master alloy is melted in a vacuum induction granulator, firstly vacuumed to 10Pa, then filled with argon gas to 1.0atm, and when all the metal materials are melted, mechanical stirring is used to make the metal liquid uniform in composition and temperature, and the metal liquid is poured into a cold water pool for cooling to form metal beads;

[0078] S2: Weigh the following components by weight:

[0079] 58 parts of oxygen-free pure zirconium, 20 parts of zirconium-niobium alloy, 3 parts of zirconium-molybdenum alloy, 7 parts of zirconium-titanium alloy, 2 parts of zirconium-silicon alloy, and 10 parts of zirconium-tin alloy;

[0080] Place oxygen-free pure zirconium, zirconium-niobium alloy, zirconium-molybdenum alloy and zirconium-titanium alloy prepared in proportion in a graphite crucible of a vacuum granulator melting chamber, and place zirconium-silicon alloy and zirconium-tin alloy in a secondary charging hopper; place raw materials and intermediate alloys in a graphite crucible, evacuate to 10Pa, and then fill with industrial pure argon; heat up to 2700°C, wait for all the furnace charge to be completely melted, stir the molten metal by a mechanical stirring device to make its temperature and composition uniform; then cool down to 2000°C, start the secondary charging device, add zirconium-silicon alloy and zirconium-tin alloy, and start the mechanical stirring device after the furnace charge is melted to make the molten metal composition and temperature uniform; then cool down to 1000°C, keep warm for 1 hour, and obtain an alloy ingot; then, perform solid solution treatment, quenching treatment and intermediate annealing treatment on the alloy ingot to forge it into a billet of a desired shape; finally, perform crystallization annealing treatment to obtain the product.

[0081] Among them, the temperature of solution treatment is 850℃, time is 2h, and water cooling is used; the temperature of quenching treatment is 800℃; the temperature of annealing treatment is 700℃; and the temperature of crystallization annealing treatment is 650℃.

[0082] In the above steps, the oxygen-free pure zirconium is an oxygen-free pure zirconium with a zirconium content of 99.95wt%; the zirconium-niobium alloy containing 10wt% is prepared by oxygen-free pure zirconium with a zirconium content of 99.95wt% and oxygen-free pure niobium with a niobium content of 99.95wt%; the zirconium-molybdenum alloy containing 10wt% is prepared by oxygen-free pure zirconium with a zirconium content of 99.95wt% and oxygen-free pure molybdenum with a molybdenum content of 99.95wt%; the zirconium-titanium alloy containing 10wt% Gold is made of oxygen-free pure zirconium with a zirconium content of 99.95wt% and oxygen-free pure titanium with a titanium content of 99.95wt%; the zirconium-silicon alloy containing 10wt% is made of oxygen-free pure zirconium with a zirconium content of 99.95wt% and oxygen-free pure silicon with a silicon content of 99.95wt%; the zirconium-tin alloy containing 10wt% is made of oxygen-free pure zirconium with a zirconium content of 99.95wt% and oxygen-free pure tin with a tin content of 99.95wt%.

[0083] Example 5

[0084] A preparation method of a dual-action hip joint Zr-Nb alloy, wherein the dual-action hip joint Zr-Nb alloy comprises the following components in weight percentage:

[0085] Nb 2.5%, Mo 0.3%, Ti 1.0%, Si 0.2%, Sn 1.0%; the balance is Zr and its inevitable impurities;

[0086] The preparation method comprises the following preparation steps:

[0087] S1: preparing the following master alloys respectively: 10%wt% zirconium-niobium alloy, 10%wt% zirconium-molybdenum alloy, 10%wt% zirconium-titanium alloy, 10%wt% zirconium-silicon alloy, and 10%wt% zirconium-tin alloy; the above master alloys are melted and cast into ingots under vacuum protective atmosphere;

[0088] Specifically, each master alloy is melted in a vacuum induction granulator, firstly vacuumed to 10Pa, then filled with argon gas to 1.0atm, and when all the metal materials are melted, mechanical stirring is used to make the metal liquid uniform in composition and temperature, and the metal liquid is poured into a cold water pool for cooling to form metal beads;

[0089] S2: Weigh the following components by weight:

[0090] 50 parts of oxygen-free pure zirconium, 25 parts of zirconium-niobium alloy, 3 parts of zirconium-molybdenum alloy, 10 parts of zirconium-titanium alloy, 2 parts of zirconium-silicon alloy, and 10 parts of zirconium-tin alloy;

[0091] Place oxygen-free pure zirconium, zirconium-niobium alloy, zirconium-molybdenum alloy and zirconium-titanium alloy prepared in proportion in a graphite crucible of a vacuum granulator melting chamber, and place zirconium-silicon alloy and zirconium-tin alloy in a secondary charging hopper; place raw materials and intermediate alloys in a graphite crucible, evacuate to 10Pa, and then fill with industrial pure argon; heat up to 2700°C, wait for all the furnace charge to be completely melted, stir the molten metal by a mechanical stirring device to make its temperature and composition uniform; then cool down to 2000°C, start the secondary charging device, add zirconium-silicon alloy and zirconium-tin alloy, and start the mechanical stirring device after the furnace charge is melted to make the molten metal composition and temperature uniform; then cool down to 1000°C, keep warm for 1 hour, and obtain an alloy ingot; then, perform solid solution treatment, quenching treatment and intermediate annealing treatment on the alloy ingot to forge it into a billet of a desired shape; finally, perform crystallization annealing treatment to obtain the product.

[0092] Among them, the temperature of solution treatment is 850℃, time is 2h, and water cooling is used; the temperature of quenching treatment is 800℃; the temperature of annealing treatment is 700℃; and the temperature of crystallization annealing treatment is 650℃.

[0093] In the above steps, the oxygen-free pure zirconium is an oxygen-free pure zirconium with a zirconium content of 99.95wt%; the zirconium-niobium alloy containing 10wt% is prepared by oxygen-free pure zirconium with a zirconium content of 99.95wt% and oxygen-free pure niobium with a niobium content of 99.95wt%; the zirconium-molybdenum alloy containing 10wt% is prepared by oxygen-free pure zirconium with a zirconium content of 99.95wt% and oxygen-free pure molybdenum with a molybdenum content of 99.95wt%; the zirconium-titanium alloy containing 10wt% Gold is made of oxygen-free pure zirconium with a zirconium content of 99.95wt% and oxygen-free pure titanium with a titanium content of 99.95wt%; the zirconium-silicon alloy containing 10wt% is made of oxygen-free pure zirconium with a zirconium content of 99.95wt% and oxygen-free pure silicon with a silicon content of 99.95wt%; the zirconium-tin alloy containing 10wt% is made of oxygen-free pure zirconium with a zirconium content of 99.95wt% and oxygen-free pure tin with a tin content of 99.95wt%.

[0094] Comparative Example 1

[0095] The difference from Example 5 is that the Zr-Nb alloy of Comparative Example 1 includes the following components in weight percentage:

[0096] Nb 2.5%, and the balance Zr and inevitable impurities thereof.

[0097] The specific preparation method is:

[0098] Weigh the following components in parts by weight:

[0099] 97.5 parts of oxygen-free pure zirconium and 2.5 parts of oxygen-free pure niobium;

[0100] Place oxygen-free pure zirconium and oxygen-free pure niobium prepared in proportion in a graphite crucible in a melting chamber of a vacuum granulator; place the raw materials in the graphite crucible, evacuate to 10Pa, and then fill with industrial pure argon; heat up to 2700°C, wait for the furnace charge to be completely melted, stir the molten metal by a mechanical stirring device to make its temperature and composition uniform; then, cool down to 1000°C, keep warm for 1 hour, and obtain an alloy ingot; then, perform solid solution treatment, quenching treatment and intermediate annealing treatment on the alloy ingot, and forge it into a billet of the desired shape; finally, perform crystallization annealing treatment to obtain the product.

[0101] Among them, the temperature of solution treatment is 850℃, time is 2h, and water cooling is used; the temperature of quenching treatment is 800℃; the temperature of annealing treatment is 700℃; and the temperature of crystallization annealing treatment is 650℃.

[0102] The other preparation methods are the same as those in Example 5 and will not be described again.

[0103] Comparative Example 2

[0104] The difference from Example 5 is that Comparative Example 2 does not contain Si, and the details are as follows:

[0105] The Zr-Nb alloy includes the following components in weight percentage:

[0106] Nb 2.5%, Mo 0.3%, Ti 1.0%, Sn 1.0%; the balance is Zr and its inevitable impurities;

[0107] Its preparation method is:

[0108] S1: preparing the following master alloys respectively: 10%wt% zirconium-niobium alloy, 10%wt% zirconium-molybdenum alloy, 10%wt% zirconium-titanium alloy, and 10%wt% zirconium-tin alloy; the above master alloys are melted and cast into ingots under vacuum protective atmosphere;

[0109] Specifically, each master alloy is melted in a vacuum induction granulator, firstly vacuumed to 10Pa, then filled with argon gas to 1.0atm, and when all the metal materials are melted, mechanical stirring is used to make the metal liquid uniform in composition and temperature, and the metal liquid is poured into a cold water pool for cooling to form metal beads;

[0110] S2: Weigh the following components by weight:

[0111] 52 parts of oxygen-free pure zirconium, 25 parts of zirconium-niobium alloy, 3 parts of zirconium-molybdenum alloy, 10 parts of zirconium-titanium alloy, and 10 parts of zirconium-tin alloy;

[0112] Place oxygen-free pure zirconium, zirconium-niobium alloy, zirconium-molybdenum alloy and zirconium-titanium alloy prepared in proportion in a graphite crucible of a vacuum granulator melting chamber, and place zirconium-tin alloy in a secondary feeding hopper; place raw materials and intermediate alloys in a graphite crucible, evacuate to 10Pa, and then fill with industrial pure argon; heat up to 2700°C, wait for the furnace charge to be completely melted, stir the molten metal by a mechanical stirring device to make its temperature and composition uniform; then, cool down to 2000°C, start the secondary feeding device, add the zirconium-tin alloy, and start the mechanical stirring device after the furnace charge is melted, so that the composition and temperature of the molten metal are uniform; then, cool down to 1000°C, keep warm for 1 hour, and obtain an alloy ingot; then, perform solid solution treatment, quenching treatment and intermediate annealing treatment on the alloy ingot, and forge it into a billet of a desired shape; finally, perform crystallization annealing treatment to obtain the product.

[0113] Among them, the temperature of solution treatment is 850℃, time is 2h, and water cooling is used; the temperature of quenching treatment is 800℃; the temperature of annealing treatment is 700℃; and the temperature of crystallization annealing treatment is 650℃.

[0114] The other preparation methods are the same as those in Example 5 and will not be described again.

[0115] Comparative Example 3

[0116] The difference from Example 5 is that the Si / Sn of Comparative Example 3 is 0.08, specifically as follows:

[0117] Nb 2.5%, Mo 0.3%, Ti 1.0%, Si 0.2%, Sn 2.5%; the balance is Zr and its inevitable impurities;

[0118] Its preparation method is:

[0119] S1: preparing the following master alloys respectively: 10%wt% zirconium-niobium alloy, 10%wt% zirconium-molybdenum alloy, 10%wt% zirconium-titanium alloy, 10%wt% zirconium-silicon alloy, and 10%wt% zirconium-tin alloy; the above master alloys are melted and cast into ingots under vacuum protective atmosphere;

[0120] Specifically, each master alloy is melted in a vacuum induction granulator, firstly vacuumed to 10Pa, then filled with argon gas to 1.0atm, and when all the metal materials are melted, mechanical stirring is used to make the metal liquid uniform in composition and temperature, and the metal liquid is poured into a cold water pool for cooling to form metal beads;

[0121] S2: Weigh the following components by weight:

[0122] 35 parts of oxygen-free pure zirconium, 25 parts of zirconium-niobium alloy, 3 parts of zirconium-molybdenum alloy, 10 parts of zirconium-titanium alloy, 2 parts of zirconium-silicon alloy, and 25 parts of zirconium-tin alloy;

[0123] Place oxygen-free pure zirconium, zirconium-niobium alloy, zirconium-molybdenum alloy and zirconium-titanium alloy prepared in proportion in a graphite crucible of a vacuum granulator melting chamber, and place zirconium-silicon alloy and zirconium-tin alloy in a secondary charging hopper; place raw materials and intermediate alloys in a graphite crucible, evacuate to 10Pa, and then fill with industrial pure argon; heat up to 2700°C, wait for all the furnace charge to be completely melted, stir the molten metal by a mechanical stirring device to make its temperature and composition uniform; then cool down to 2000°C, start the secondary charging device, add zirconium-silicon alloy and zirconium-tin alloy, and start the mechanical stirring device after the furnace charge is melted to make the molten metal composition and temperature uniform; then cool down to 1000°C, keep warm for 1 hour, and obtain an alloy ingot; then, perform solid solution treatment, quenching treatment and intermediate annealing treatment on the alloy ingot to forge it into a billet of a desired shape; finally, perform crystallization annealing treatment to obtain the product.

[0124] Among them, the temperature of solution treatment is 850℃, time is 2h, and water cooling is used; the temperature of quenching treatment is 800℃; the temperature of annealing treatment is 700℃; and the temperature of crystallization annealing treatment is 650℃.

[0125] The other preparation methods are the same as those in Example 5 and will not be described again.

[0126] Performance Testing

[0127] The comprehensive mechanical properties such as tensile strength, yield strength, surface hardness, elastic modulus, etc. were tested for Examples 1-5 and Comparative Examples 1-2. The test results are shown in Table 1 below.

[0128] Table 1

[0129]

[0130] It can be seen from the above table that compared with Comparative Examples 1 and 2, Examples 1-5 have improved their surface hardness and thus their wear resistance due to the addition of elements such as Mo, Ti, Si and Sn; Comparative Example 3 has increased the Sn content due to the change in its Si / Sn ratio, resulting in a corresponding decrease in its other properties.

[0131] At the same time, the tensile strength Rm of the alloys of Examples 1-5 is greater than 650 MPa, and the elastic modulus is below 70 Gpa, which meets the application requirements of dual-motion hip joints and other biomedical fields.

[0132] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.

Claims

1. A method for preparing a dual-action hip joint Zr-Nb alloy, characterized in that: The dual-action hip joint Zr-Nb alloy comprises the following components in weight percentage: Nb 1.0-2.5%, Mo 0.3-1%, Ti 0.7-1.2%, Si 0.2-0.6%, Sn 1.0-2.0%, and the balance is Zr and its inevitable impurities; the mass ratio of Si to Sn is 0.2-0.3; The preparation method comprises the following preparation steps: S1: preparing the following master alloys respectively: 10%wt% zirconium-niobium alloy, 10%wt% zirconium-molybdenum alloy, 10%wt% zirconium-titanium alloy, 10%wt% zirconium-silicon alloy, and 10%wt% zirconium-tin alloy; the above master alloys are melted and cast into ingots under vacuum protective atmosphere; S2: Weigh the following components in parts by weight: 28-68 parts of oxygen-free pure zirconium, 10-25 parts of zirconium-niobium alloy, 3-10 parts of zirconium-molybdenum alloy, 7-12 parts of zirconium-titanium alloy, 2-6 parts of zirconium-silicon alloy, and 10-20 parts of zirconium-tin alloy; place the oxygen-free pure zirconium, zirconium-niobium alloy, zirconium-molybdenum alloy, and zirconium-titanium alloy prepared in proportion in a graphite crucible in the melting chamber of a vacuum granulator, and place the zirconium-silicon alloy and zirconium-tin alloy in a secondary feeding hopper; place the raw materials and the intermediate alloy in a graphite crucible, evacuate to 10Pa-20Pa, and then fill it with industrial pure argon; raise the temperature to 2650°C-2700°C, and wait for the furnace to After all the materials are melted, the molten metal is stirred by a mechanical stirring device to make its temperature and composition uniform; then, the temperature is lowered to 2000℃~2200℃, the secondary feeding device is started, and the zirconium-silicon alloy and zirconium-tin alloy are added. After the furnace charge is melted, the mechanical stirring device is started to make the molten metal composition and temperature uniform; then, the temperature is lowered to 1000℃~1200℃, and kept warm for 1h-1.5h to obtain an alloy ingot; then, the alloy ingot is subjected to solid solution treatment, quenching treatment and intermediate annealing treatment to be forged into a billet of the desired shape; finally, a crystallization annealing treatment is performed to obtain the product.

2. The method for preparing the dual-action hip joint Zr-Nb alloy according to claim 1, characterized in that: The dual-motion hip joint Zr-Nb alloy comprises the following components in weight percentage: Nb 1.0-2.5%, Mo 0.5-0.8%, Ti 0.9-1.1%, Si 0.4-0.6%, Sn 1.0-2.0%, and the balance is Zr and inevitable impurities thereof.

3. The method for preparing the dual-action hip joint Zr-Nb alloy according to claim 2, characterized in that: The total content of the inevitable impurities does not exceed 0.1%.

4. The method for preparing the dual-action hip joint Zr-Nb alloy according to claim 1, characterized in that: In step S1, a zirconium-niobium alloy containing 10%wt% is prepared by using oxygen-free pure zirconium with a zirconium content of 99.95wt% and oxygen-free pure niobium with a niobium content of 99.95wt%; a zirconium-molybdenum alloy containing 10%wt% is prepared by using oxygen-free pure zirconium with a zirconium content of 99.95wt% and oxygen-free pure molybdenum with a molybdenum content of 99.95wt%; a zirconium-titanium alloy containing 10%wt% is prepared by using oxygen-free pure zirconium with a zirconium content of 99.95wt% and oxygen-free pure titanium with a titanium content of 99.95wt%; a zirconium-silicon alloy containing 10%wt% is prepared by using oxygen-free pure zirconium with a zirconium content of 99.95wt% and oxygen-free pure silicon with a silicon content of 99.95wt%; a zirconium-tin alloy containing 10%wt% is prepared by using oxygen-free pure zirconium with a zirconium content of 99.95wt% and oxygen-free pure tin with a tin content of 99.95wt%.

5. The method for preparing the dual-action hip joint Zr-Nb alloy according to claim 1, characterized in that: In step S2, the solution treatment is performed at a temperature of 800°C-900°C, for a time of 1h-3h, with water cooling.

6. The method for preparing the dual-action hip joint Zr-Nb alloy according to claim 1, characterized in that: In step S2, the temperature of the quenching treatment is 800°C-900°C.

7. The method for preparing the dual-action hip joint Zr-Nb alloy according to claim 1, characterized in that: In step S2, the temperature of the annealing treatment is 600°C-700°C.

8. The method for preparing the dual-action hip joint Zr-Nb alloy according to claim 1, characterized in that: In step S2, the temperature of the crystallization annealing treatment is 650°C-750°C.

Citation Information

Patent Citations

  • Low-elasticity-modulus high-fatigue-strength biologic implantable titanium alloy and preparation method thereof

    CN105420549A

  • Low-melting-point Zr-2. 5Nb alloy material and alloy product

    CN115725875A